Environmental, Social, Governance and Gen-der Diversity Under the Adoption of European Directive 2014/95/EU - Christianna Chimonaki; Stelios Papadakis; Christos Lemonakis (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- Does Gender Diversity positively or negatively affect the non-financial information on ESG? Motivation- This research explores the connection between ESG and the synthesis of the Board of Directors. More explicitly, we explore if the board's Gender Diversity improves non-financial information on ESG. Also, the effect of board gender diversity on ESG is under investigation as the findings in the current literature about the synthesis of board gender diversity are mixed. Considering this gap, this research tries to understand if Gender Diversity positively or negatively affects the non-financial information on ESG. Idea- This research article aims to study the relationship between gender diversity on board and European companies' environmental, social, and governance (ESG) ratings. It also examines the potential impact of European Directive 2014/95/EU, which re-quires disclosure of non-financial information, on this relationship. Data- The investigation used the dataset of 5,380 observations from 20 European countries from 2013 to 2022. Tools- The association between the ESG ratings and control variables was examined using regression analysis. Findings- The investigation results confirm a statistically significant impact between gender diversity and ESG performance ratings. The findings confirm conclusions drawn in other research studies. The adoption and enforcement of EU Directive 2014/95/EU had a remarkable and positive impact on European firms' ESG policies, as shown by statistical significance in several regression models. Gender diversity on company boards positively impacted all ESG models except the Governance Pillar Score. The investigation shows the importance of board synthesis, gender diversity, and additional variables concerning ESG reporting practices. Contribution- This research explores the connection between ESG and the synthesis of the Board of Directors. More explicitly, we explore if the board's Gender Diversity improves non-financial information on ESG. Also, the effect of board gender diversity on ESG is under investigation as the findings in the current literature about the synthe-sis of board gender diversity are mixed. Considering this gap, this research tries to un-derstand if Gender Diversity positively or negatively affects the non-financial infor-mation on ESG.
Keywords: M41; 650; Environmental; Social; Governance; gender diversity; sustainable governance; Euro-pean Union; Accounting